(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the use of mnemonic techniques, which are important for the development of oral and written speech in students, their successful participation in the educational process, and the ability to express their thoughts independently, and to improve the memory of students, to use information effectively commenting and reacting to the formation of acquisition and recall skills.